(untitled) (Research, Society and Development, 2021)
The following paper describes the opportunities and challenges in Mexican universities that teach foreign languages face during the health contingency caused by Covid-19. This quantitative study gathered information from a survey sent to the heads of international affairs offices of Mexican universities affiliated to the National Association of Higher Education Institutions and Universities (ANUIES for its Spanish acronym) in Mexico. Results map the future of language teaching in the country and the new tasks to be taken within an educational context and university language policy, in addition to designing Online Emergency Courses (CER for its Spanish acronym,) training, and developing new ways to teach languages. Moreover, to follow up the good performance of some programs, which sets the standard to guide our efforts toward a new way of teaching with a language policy that fits this new normality.